A COMPARATIVE STUDY OF KNOWLEDGE REGARDING EMERGENCY CARE DURING DISASTER BETWEEN COMMUNITY HEALTH VOLUNTEERS WORKING IN TSUNAMI-AFFECTED AND NON-AFFECTED AREAS IN ACEH PROVINCE, INDONESIA - Anda Kamal (Idea Nursing Journal, 2013)
Purpose: This paper is a report of a survey to describe and compare the level of knowledge and comparethese knowledge between community health volunteers (CHVs) working in the tsunami affected and nonaffectedareas in Aceh Province, Indonesia Method: 144 CHVs from six districts in Aceh were studied duringNovember 2011 to January 2012 to evaluate their level knowledge regarding emergency care during disasterbetween CHVs working in Tsunami affected areas and non Tsunami affected areas. The knowledge wasassessed by using the Community Health Volunteers’ Knowledge Regarding Emergency Care Questionnaire(CHVK-ECQ) with 30-statement true/false. The composite scores of each area and the total score werecalculated and transformed to percentage for ease of presentation.Results: Overall, the CHVs’ knowledge inemergency care during disaster in Aceh was at a high level in both groups. However, subjects in non-affectedareas had significantly higher mean rank of the overall knowledge than those in the affected areas (p = .02).In the tsunami area the highest mean score was for the disaster triage dimension (M= 80.62%), and thelowest mean score was in the first Aid (60.48 %). And on the contrary in the non tsunami areas the highestmean score was for First Aid (84.52 %) and the lowers mean score was for disaster triage (64. 38 %).Conclusion: This finding indicated that although both groups had high levels of overall knowledge, educationprogram for improved knowledge in the areas of first aid, team organization, and disaster triage should beestablished to refresh the CHVs’ knowledge and skills for the disaster management.Keywords: Knowledge, skills, community health volunteers, and natural disaster